2006
DOI: 10.1098/rstb.2006.1822
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of exposure assessment in health studies of Gulf War veterans

Abstract: A variety of exposures have been investigated in Gulf War veterans' health studies. These have most commonly been by self-report in a postal questionnaire but modelling and bio-monitoring have also been employed. Exposure assessment is difficult to do well in studies of any workplace environment. It is made more difficult in Gulf War studies where there are a number and variety of possible exposures, no agreed metrics for individual exposures and few contemporary records associating the exposure with an indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 82 publications
2
18
0
Order By: Relevance
“…Exposure assessments a challenge in military health research, 21 and most studies still rely heavily on self‐reported exposure data, which is of course subject to recall bias. Ability to accurately and objectively assess the exposure(s) of individuals or groups is a critical element of health surveillance, as it provides the opportunity to assess the level of exposure that results in ill‐health 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Exposure assessments a challenge in military health research, 21 and most studies still rely heavily on self‐reported exposure data, which is of course subject to recall bias. Ability to accurately and objectively assess the exposure(s) of individuals or groups is a critical element of health surveillance, as it provides the opportunity to assess the level of exposure that results in ill‐health 22 .…”
Section: Discussionmentioning
confidence: 99%
“…As such, self-report is frequently used as a surrogate for deployment-related exposures in the vast majority of research studies and clinical encounters. 9 There is no standardized validated questionnaire used to assess veterans' occupational and environmental exposures in theater. In line with occupational health studies and most Gulf War studies, exposures in this study were assessed using checklist questionnaires because studies demonstrate that qualitative rating of perceived exposures tends to correlate reasonably well with an external standard.…”
Section: Exposure Concernsmentioning
confidence: 99%
“…In line with occupational health studies and most Gulf War studies, exposures in this study were assessed using checklist questionnaires because studies demonstrate that qualitative rating of perceived exposures tends to correlate reasonably well with an external standard. 9,10 For the purposes of the WRIISC clinical evaluation, an exposure assessment questionnaire measure was created by one of the authors (R.T.), an occupational and environmental medicine physician who specializes in postdeployment environmental exposure concerns. Development of this questionnaire was based on clinical experience and questionnaires used in previous studies, 4,9,[11][12][13][14] and the questions were adapted to address specific exposures pertinent to deployment to Iraq/Afghanistan as well as the level of concern associated which each reported exposure.…”
Section: Exposure Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study examining the accuracy of reported work‐related injuries demonstrates that the integrity of self‐reported injury data decreases when recall is greater than 2 months . Other studies have identified similar issues with time‐dependent recall . Survey fatigue, identified as a lack of interest in survey participation has led to a general decline in response rates to survey‐based data collection efforts in public health research…”
Section: Introductionmentioning
confidence: 99%